Analisis Pengaruh Religiusitas Dan Islamic Branding Terhadap Kinerja Umkm Muslim Di Indonesia Dengan Literasi Keuangan Sebagai Variabel Mediasi - Hanifah, Putri Adriyani; DR., Zulpahmi SE., M.Si.; Legowati, M.Si, Diah Ayu (ITB AAS INDONESIA Surakarta, 2024)
The number of MSMEs in Indonesia has increased every year. Indonesia is one of the countries with the largest Muslim population in the world, amounting to 237.04 million people, or 86.93% of Indonesia's population is Muslim at the end of 2021. This study aims to examine the relationship between religiosity and Islamic branding on the performance of Muslim Micro, Small and Medium Enterprises (MSMEs) in Indonesia. This study also examines the mediating role of financial literacy (financial attitudes, financial awareness, and financial knowledge) on the relationship between religiosity, Islamic branding, and MSME performance with analysis techniques using PLS-SEM. The population in this study were MSMEs in Indonesia. The sampling technique in the study used purposive sampling technique with a total sample of 335 Muslim MSME respondents in Indonesia. The results show that religiosity has a positive and significant effect on attitudes, awareness and financial knowledge. Islamic branding has a positive and significant effect on attitudes, awareness and financial knowledge. Attitude, awareness and financial knowledge have a positive and significant effect on MSME performance. Religiosity affects MSME performance through mediation of attitudes, awareness and financial knowledge. Islamic branding affects performance through financial awareness and knowledge, but not financial attitudes.